2003
DOI: 10.1200/jco.2003.10.106
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome Differences in Supraglottic Cancer Between Ontario, Canada, and the Surveillance, Epidemiology, and End Results Areas of the United States

Abstract: There are large differences in the management of supraglottic cancer between the SEER areas of the United States and Ontario. Long-term larynx retention was higher in Ontario, where radiotherapy is widely regarded as the treatment of choice and surgery is reserved for salvage. In stages I to III, survival was similar in the two regions despite the differences in treatment policy. In stage IV, there may be a small survival advantage in the U.S. SEER areas related to the higher use of primary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 33 publications
0
71
0
1
Order By: Relevance
“…The KRCC outpatient chart is appropriate for a study of patients with head and neck cancer because it contains a complete relevant history and physical examination for each patient and because the decisions on treatment are almost invariably made in the outpatient setting. The outpatient charts from the regional cancer treatment centers of Cancer Care Ontario have been used in our research unit for numerous studies [12][13][14].…”
Section: Data Sourcementioning
confidence: 99%
“…The KRCC outpatient chart is appropriate for a study of patients with head and neck cancer because it contains a complete relevant history and physical examination for each patient and because the decisions on treatment are almost invariably made in the outpatient setting. The outpatient charts from the regional cancer treatment centers of Cancer Care Ontario have been used in our research unit for numerous studies [12][13][14].…”
Section: Data Sourcementioning
confidence: 99%
“…Whereas outcomes for supraglottic SCCa vary, they are generally poor and significantly worse than their glottic counterpart, with 5‐year overall survival ranging from 47% to 56% for stage III disease and 29% to 45% for stage IV disease . This can be attributed to the location of malignancy, allowing it to remain asymptomatic until it has reached an advanced stage .…”
Section: Introductionmentioning
confidence: 99%
“…These differences are in keeping with the findings of previous survey research and clinical studies that have compared medical and surgical practice patterns between Canadian and American surgeons. [6][7][8][9][10][11] These studies have consistently reported that American surgeons and physicians are more likely to order diagnostic tests and recommend surgery and interventional procedures compared with their Canadian counterparts. To our knowledge, no previous studies have specifically compared gastrointestinal surgery practice patterns between the 2 countries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that there are differences in clinical practice between Canadian and American physicians. [6][7][8][9][10][11] However, there are few data comparing general surgical practice patterns between the 2 countries. The purpose of this study was to compare the practice patterns of Canadian and American colorectal surgeons regarding the surgical management of ulcerative colitis.…”
mentioning
confidence: 99%